Concentration of amikacin sulphate in synovial fluid when given in combination with dexamethasone phosphate in intravenous regional limb perfusion in standing horses. Issue 4 (20th March 2022) - Gustafsson, Kajsa; Tatz, Amos J.; Britzi, Malka; Dahan, Roee; Sutton, Gila A.; Kelmer, Gal
Abstract: Eight horses underwent IVRLP at two occasions through a 23‐gauge 2 cm long butterfly catheter. Regional anaesthesia of the ulnar, median and medial cutaneous antebrachial nerves was performed prior, and an 8 cm rubber tourniquet was placed on the proximal radius for 30 minutes following the infusion. The first infusion consisted of 2 g of amikacin sulphate and 10 mg of dexamethasone phosphate diluted with 0.9% NaCl to a total volume of 100 ml. The second perfusion was performed after a 2‐week washout period, the same protocol was used but without dexamethasone phosphate. Synovial fluid samples were collected from the metacarpophalangeal joint at T = 0, 0.5, 2, 12, 24 and 36 h post‐infusion. Synovial fluid amikacin sulphate concentrations were determined by use of liquid chromatography/tandem mass‐spectrometry. All horses ( n  = 8) remained healthy throughout the study, and no adverse effects associated with the study were encountered. No statistically significant differences were found in synovial fluid amikacin sulphate concentrations between the treatment and the control group at any of the time points. In conclusion, dexamethasone phosphate can be used in IVRLP concomitantly with amikacin sulphate in cases of distal limb inflammation and pain without decreasing the synovial fluid concentration of amikacin sulphate.